Catch and selectivity parameters of the anastomid fish Schizodon nasutus using gillnets in the Jurumirim reservoir (São Paulo, Brazil) - Garcia-Mellado, A.; Oliva-Paterna, F. J.; Carvalho, E. D.; Torralva, M. (Unione Zoologica Italiana, 2002)
Catch and selectivity parameters using gillnets were calculated for Schizodon nasutus in the Jurumirim reservoir on the Parana-panema River in southern Brazil. The simple gillnets used were made of monofilament nylon of 30 to 140 mm mesh size an of different heights. The relative abundance of the S. nasutus caught was analysed monthly and a positive relationship was found between catches per unit effort in number and biomass. The relative catches were more abundant for the nets of 40 and 50 mm, mesh size. Catches were characterized by clear temporal variations and a predominance of medium size fish throughout the study period. The selectivity curve of gillnets for S. nasutus in this ecosystem was obtained. The catch obtained was compared with the available catch for each mesh size, and the available catch for a certain length of fish was calculated starting from the theoretical selectivity curve. The 50 mm mesh size gillnet showed the best fit between real and available captures and was considered the most suitable, because a smaller mesh size resulted in a catch of predominantly immature specimens. It is expected that these results will contribute to improving management strategies for conservation of resources. Parameters such as the minimum catch length advisable or the mesh size permitted for a given species are indispensable for such decision-making.
Keywords: freshwater fish; fishery management; reservoir; catches per unit effort; selectivity; gillnet